Boolean Algebra, Major Defects, Minor Defects, and Hemostasis - Hathhorn, Thomas K. (Thrombosis and Haemostasis, 1977)
The purpose of this paper is to show how simple application of Boolean algebra to hemostasis can be used in the diagnosis and teaching of problems in coagulation. By utilizing a simple Venn diagram with plasma factors, hemostatic plug and vascular factors (includes local lesions) as categories and dividing defects in these areas arbitrarily into major and minor defects, a simple holoistic approach is revealed. Any major defect (e.g. < 5% AHG or a large lesion) may result in persistent hemorrhage. One minor defect in any area of the diagram does not alter hemostasis clinically or cause spontaneous or persistent hemorrhage. Two minor defects or more in any area may be associated with spontaneous hemorrhage (e.g. 20% AHG and aspirin ingestion). If one sees a bleeding patient and one minor defect is noted, look for a second minor defect. Utilizing this approach to common everyday problems in coagulation with trauma or pathologic lesions constituting one defect reveals the submerged part of the iceberg of treatable hemorrhagic disease. Listing of major and minor defects with illustrative case histories will be presented.